The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.12.14.520469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paradoxical improvement of cognitive control in older adults under dual-task walking conditions is associated with more flexible reallocation of neural resources: A Mobile Brain-Body Imaging (MoBI) study

Abstract: Combining walking with a demanding cognitive task is traditionally expected to elicit decrements in gait and/or cognitive task performance. However, it was recently shown that, in a cohort of young adults, most participants paradoxically improved performance when walking was added to performance of a Go/NoGo response inhibition task. The present study aims to extend these previous findings to an older adult cohort, to investigate whether this paradoxical improvement when dual-tasking is observed in healthy old… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 128 publications
(215 reference statements)
1
4
0
Order By: Relevance
“…Lower amplitude alterations to anticipatory and reactive processes, coupled with deteriorating behavioral performance as demands increased, may reflect reduced cognitive flexibility in older adults. These results replicated, and expanded upon the findings of our previous studies (Malcolm et al, 2015;Patelaki, Foxe, Mantel, et al, 2023;Patelaki et al, 2022;Patelaki, Foxe, McFerren, & Freedman, 2023;Richardson et al, 2022).…”
Section: Summary Of Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Lower amplitude alterations to anticipatory and reactive processes, coupled with deteriorating behavioral performance as demands increased, may reflect reduced cognitive flexibility in older adults. These results replicated, and expanded upon the findings of our previous studies (Malcolm et al, 2015;Patelaki, Foxe, Mantel, et al, 2023;Patelaki et al, 2022;Patelaki, Foxe, McFerren, & Freedman, 2023;Richardson et al, 2022).…”
Section: Summary Of Resultssupporting
confidence: 85%
“…Dual-task effects on performance were categorized into "improvement", "no change", or "cost" according to the procedure used by Patelaki and colleagues (Patelaki, Foxe, Mantel, et al, 2023;Patelaki et al, 2022). Walking-minus-sitting d' values and response times for each participant were defined as dual-task improvement or cost if they fell outside the 95% confidence interval of the normal distribution centered around a mean of zero and with a standard deviation equal to the variance of the entire cohort of younger and older adults.…”
Section: Procedurementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, walking speed during DTs decreased when compared with walking alone, which is consistent with previous research findings (Doi et al, 2013; Hall et al, 2011; Mirelman et al, 2014). However, some studies have shown either maintained or improved gait integrity and cognitive performance during DT walking (De Sanctis et al, 2014; Fraser et al, 2016; Hamacher et al, 2019; Hausdorff, 2005; Patelaki et al, 2023, 2023; Richardson et al, 2022); these findings were believed to be related to neural circuit flexibility compensation (Richardson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Further research has indicated that a concurrent cognitive task may reduce the input from high‐level cognitive processes for the control of gait, thus resulting in deterioration in walking performance (Mirelman et al, 2014; Wrightson et al, 2016). However, some studies have shown either maintained or improved gait integrity and cognitive performance during DT walking (De Sanctis et al, 2014; Fraser et al, 2016; Hamacher et al, 2019; Hausdorff, 2005; Patelaki et al, 2023, 2023; Richardson et al, 2022). Assessing gait and cognitive interference simultaneously can shed light on the possible influence of task prioritization strategies on DT performance (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%